2011
DOI: 10.1289/ehp.1103548
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Motor Function among Children in Bangladesh

Abstract: Background: Several reports indicate that drinking water arsenic (WAs) and manganese (WMn) are associated with children’s intellectual function. Very little is known, however, about possible associations with other neurologic outcomes such as motor function.Methods: We investigated the associations of WAs and WMn with motor function in 304 children in Bangladesh, 8–11 years of age. We measured As and Mn concentrations in drinking water, blood, urine, and toenails. We assessed motor function with the Bruininks-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 57 publications
3
104
2
1
Order By: Relevance
“…It also causes other health effects, including vascular diseases, probably diabetes mellitus and hypertension, peripheral neuropathy, and poor intellectual function (Rahman et al 1999;Kwok et al 2007;Heck et al 2008). Children are the most threatened group, especially regarding neurological damage, since the brain undergoes changes during childhood that can have a lasting impact on behavior and cognitive processing (Calderon et al 2001;Wasserman et al 2007;Von Ehrenstein et al 2007;Parvez et al 2011).…”
mentioning
confidence: 99%
“…It also causes other health effects, including vascular diseases, probably diabetes mellitus and hypertension, peripheral neuropathy, and poor intellectual function (Rahman et al 1999;Kwok et al 2007;Heck et al 2008). Children are the most threatened group, especially regarding neurological damage, since the brain undergoes changes during childhood that can have a lasting impact on behavior and cognitive processing (Calderon et al 2001;Wasserman et al 2007;Von Ehrenstein et al 2007;Parvez et al 2011).…”
mentioning
confidence: 99%
“…In that study 18% of the children who were exposed to arsenic-contaminated water (arsenic levels >50 μg/L) showed abnormal mental development and reduced intellectual function compared to the children who did not drink arsenic-contaminated water [70]. Another study conducted among children aged 8-11 years revealed an inverse association of arsenic exposure through drinking water with lower developmental scores of the children [71]. Arsenic is a known carcinogen and has the potential to produce cancers at multiple sites, notably in the skin, bladder, kidneys, prostate, and lungs [56][57][58].…”
Section: Suspected Case Showing Melanosis or Keratosis After Excludinmentioning
confidence: 99%
“…On the other hand, inverse associations have also been reported for a variety of nonverbal endpoints, including Performance IQ and Processing Speed [33,31], individual subtests of the Wechsler scales that contribute to Performance IQ, such as Object Assembly (simple jigsaw puzzles) and Picture Completion (attention to visual detail) [34], visual-spatial abilities and sequencing [36], and motor skills such as body coordination and fine manual control [49].…”
Section: Most Sensitive Endpointsmentioning
confidence: 99%